Leading the Future of Medical Education: A Dean’s Perspective on MBBS (Bachelor of Medicine and Bachelor of Surgery) curriculum Design of Purbanchal University, Nepal (Purbanchal University Health Journal, 2024)
The development of the MBBS curriculum at Purbanchal University (PU) signifies a monumental advancement in medical education in Nepal. This article delves into the processes, methodologies, and guiding principles employed in the creation of the curriculum, emphasizing its alignment with global standards, national health needs, and modern educational practices. The curriculum’s innovative elements, such as the SPICE (Student-centered, Problem-based, Integrated, Community-based, and Elective) model and competency-based education, alongside its comprehensive structure integrating basic and clinical sciences, aim to produce proficient medical graduates equipped to meet both local and international healthcare demands.